P163Stromal derived factor 1-a protects human heart tissue from simulated ischaemia-reperfusion injury. (15th July 2014) - Malik, A; He, Z; Sivaraman, V; Davidson, SM; Walker, JM; Yellon, DM
Abstract: Purpose: Whether, stromal cell-derived factor 1 αlpha (SDF-1α) can protect human heart tissue is not known, and is investigated here using isolated human atrial trabeculae exposed to simulated ischaemia-reperfusion injury (IRI). Methods: Atrial trabeculae were isolated from right atrial appendage tissue harvested from consented patients undergoing elective cardiac bypass surgery (REC 00/0275). They were suspended in organ baths and superfused with normoxic Tyrode's solution at 37.0°C with a field stimulation of 1 Hz. Atrial trabeculae were randomised to receive: (1) Control group (N=10): 60 minutes simulated ischaemia (SI, hypoxic solution+3 Hz field stimulation) followed by 60 minutes reperfusion. After 60 minutes reperfusion the recovery of baseline contractile function (expressed as a %) was determined; (2) SDF-1α group (N=10): Trabeculae were perfused with SDF-1α (25ng/ml) for 30 minutes prior to SI; (3) SDF-1α+AMD3100 group (N=7): Trabeculae were perfused with SDF-1α (25ng/ml) for 30 minutes prior to SI, with AMD3100 (10mcg/ml), a specific SDF-1α/CXCR4 receptor blocker, given 10 minutes prior to SDF-1α; (4) AMD 3100 group (N=4): Trabeculae were treated with AMD3100 given 40 minutes prior to SI. Results: (see figure 1). Pre-treatment of human atrial trabeculae with SDF-1α prior to simulated IRI improved the % recovery of baseline contractile function when compared to control (52±2% with SDF-1α versus 28±2% in control; p<0.05). This cardioprotective effect was significantly reduced by AMD3100 when compared to SDF-1α alone (24±2% with SDF-1α+AMD100; p<0.05). AMD3100 itself had no effect on functional recovery when compared to control (30±4% with AMD3100 versus 28±2% with control; p>0.05). Conclusion: In this study we demonstrate the cardioprotective effect of SDF-1α in human heart tissue.